Estimación de series de salarios regionales en Chile - Jorge Dresdner; Carlos Sanhueza (Estudios de Economía, 2009)
– Monthly wage series with quarterly periodicity between December 1994 and December 2004 for thirteen regions in Chile are presented in this paper. These series are based on the information recollected by the Superintendencia de Fondos de Pensiones (Pensions Fund Superintendence), but are corrected for truncation and censoring bias. The comparative analysis of corrected and non-corrected series indicates that the series show a statistically diferentiated behavior. The non-corrected wage series are not good predictors of the corrected series. Thus, to develop regional wage analysis, based on this information source, it is preferable to use the corrected series presented in this paper.
Keywords: J31; R11; R23; 330; regional wages; estimation; truncation; censored; Regionale Lohnstruktur; Chile